Psychological Aspects and Coping Strategies Among Children of Baal Sudhar Griha, Morang - Mehta, Shalini; Karn, Basant Kumar; Chaudhary, Ramananda; Lama, Sami (Journal of Biratnagar Nursing Campus, 2023)
Background: Child development incorporates physical growth as well as intellectual, language, emotional and social development. During Juvenile home stay they are unable to fulfill their need and requirements of children over the duration of sentences, so many children are compromising their childhood as well as mental health. Assessment of psychological aspects and coping strategies of the children to identify their mental health and their measures to cope or overcome ups and down, also to identify the root causes of offending behavior and measures to prevent such behavior. Assessment of psychological aspects and ability to cope among children of Baal Sudhar Griha, Morang was the objective.Methods: Descriptive cross sectional study was adopted. At present 152 children residing at Baal Sudhar Griha of Morang were included by population enumerate sampling method. To assess socio-demographic variables semi- constructed structured questionnaire was used. To assess psychological aspects and coping strategies DASS-21 and Brief Cope was used. Descriptive and Inferential statistics were used for data analysis.Results: Most of the children (46%) were facing severe form of psychological challenges like stress, anxiety, depression. Similarly majority (67.1%) of the respondents were found to have emotion focused coping strategies used by the children of Baal Sudhar Griha.Conclusion: Study result reveals that majority of the children were facing severe form of stress, anxiety and depression. Around half of children used emotion focused coping strategies to cope such psychological distress in their day today life.